(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Worldwide 250 million people are suffering from Hepatitis B Virus (HBV) infection. Treatment with antiviral drugs improve survival and quality of life by preventing disease progression and Hepatocellular Carcinoma (HCC). Indications for antiviral treatment primarily based on serum HBV DNA, Alanine Aminotransaminase (ALT) and severity of liver disease. Entecavir is one of the potent antiviral drug against hepatitis B virus. This study has been conducted to evaluate the efficacy of entecavir in both Hepatitis Be Antigen (HBeAg) positive and HBeAg negative treatment naïve Bangladeshi patients. Materials and methods: A total 205 patients were enrolled in this study from 2010-2014 in outpatients department of Hepatology in Chattogram Medical College Hospital. All patients got Entecavir 0.5 mg daily and followed at 12 weeks, 24 weeks & 52 weeks of the treatment by ALT, HBsAg, HBe- Ag and HBV DNA. 55 patients lost during follow- up and 150 patients completed 52 weeks treatment and finally evaluated. Results: The mean HBV DNA at baseline was 26.4 x 109 ± 7.4 x 109 copies / ml which was decreased to 2.2 x 106 ± 1.4 x 105 copies/ml at the end of 52 weeks which was statistically significant. At 52 weeks 118 (78%) CHB patient became HBV DNA negative. The mean ALT level before treatment were 96.1 ± 70.9 U/L which were 39.7 ± 11.98 U/L at the end of 52 weeks. At 52 weeks of treatment 78 (71.5%) became HBeAg negative. Conclusion: Entecavir significantly suppress HBV DNA level as well as normalization of aminotransfersae level. It has significant influences on HBeAg negativity in HBeAg positive chronic hepatitis B patients. JCMCTA 2019 ; 30 (1) : 12-15